MODEL MEDIA PEMBELAJARAN SEJARAH DI SMA BERBASIS VISUALISASI INTERAKSI SOSIAL MASYARAKAT ZAMAN KERAJAAN SRIWIJAYA UNTUK MENINGKATKAN SIKAP TOLERANSI - Susilo, Agus; Sariyatun, S.; Suryani, Nunuk (Sebelas Maret University (UNS), 2014)
This development research aims to produce effective learning media to meet the needs of teachers and students in teaching and learning in schools. The resulting learning media is media-based history teaching social interaction visualization era Sriwijaya Kingdom to improve the tolerance of students in SMAN 5 Surakarta where the use of social media interaction visualization era Sriwijaya Kingdom.In this development research, researchers were developed media visualization. This type of research is the development of media development with ADDIE (Analysis, Design, Development, Implementation, Evaluation). The study population was class X IPS SMAN 5 Surakarta, the study sample is determined in three classes, X IPS 1 as a class experiment, X IPS 2 as the control class, and the class as a class X IPS 3 trials. Instrument used to collect data were observation, interviews, pre-test tolerance questionnaire and pre-test. Test instrument questionnaires and achievement tests include the validation of items and reliability.The results of research showed: (1) Type of instructional media history at the senior high school has been used is the type of media power point, student worksheets and textbooks, (2) Model medium of learning history in senior high school `based visualization of social interaction of society era of Sriwijaya done through the stages ADDIE and generate media visualization by video forms of learning that experienced numerous revisions and has been validated by an expert media and materials as well as further successfully tested in the classroom X IPS 3 SMAN 5 Surakarta. (3) Test the effectiveness of instructional media History based visualizationsocial interaction of era Sriwijaya Kingdom is done by comparing the value of posttest experimental class and control class with a significance level of 5% and it is known that with thit (3.76) ttab (2.00) for attitude tolerance, then the decision-Ho is rejected. It can be concluded that the medium of teaching history in senior high school based social interaction visualization of era Sriwijaya effective for increasing tolerance.